2016
DOI: 10.1074/jbc.m115.700609
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelets Utilize Cycloxygenase-1 to Generate Dioxolane A3, a Neutrophil-activating Eicosanoid

Abstract: Eicosanoids are important mediators of fever, pain, and inflammation that modulate cell signaling during acute and chronic disease. We show by using lipidomics that thrombin-activated human platelets generate a new type of eicosanoid that both stimulates and primes human neutrophil integrin (Mac-1) expression, in response to formylmethionylleucylphenylalanine. Detailed characterization proposes a dioxolane structure, 8-hydroxy-9,11-dioxolane eicosatetraenoic acid (dioxolane A3, DXA3). The lipid is generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 38 publications
6
36
0
Order By: Relevance
“…21 Similarly, NLRP12 (Pypaf-7) is crucial for neutrophil recruitment in other models of infection, 22 including to the lungs, 23 whereas (among its other actions) COX-1 generates eicosanoids, which activate neutrophils. 24 We have also shown that neutrophil markers strongly colocalise with IL-10 in human tuberculous granulomas. 20 Our gene expression data, therefore, suggested a role for neutrophils in TB-IRIS pathogenesis and we examined this in another patient cohort, subsequently recruited in Cape Town.…”
Section: Tb-iris Is Characterized By Neutrophiliamentioning
confidence: 52%
“…21 Similarly, NLRP12 (Pypaf-7) is crucial for neutrophil recruitment in other models of infection, 22 including to the lungs, 23 whereas (among its other actions) COX-1 generates eicosanoids, which activate neutrophils. 24 We have also shown that neutrophil markers strongly colocalise with IL-10 in human tuberculous granulomas. 20 Our gene expression data, therefore, suggested a role for neutrophils in TB-IRIS pathogenesis and we examined this in another patient cohort, subsequently recruited in Cape Town.…”
Section: Tb-iris Is Characterized By Neutrophiliamentioning
confidence: 52%
“…It was reported that: aspirin can inhibit the formation of prostaglandins and thromboxane A 2 (promote platelet aggregation and vasoconstriction by inhibiting of the COX‐1 enzyme irreversibly). And cox‐1 can activate platelet …”
Section: Discussionmentioning
confidence: 99%
“…Platelet eicosanoids (TXA2, 12‐HETE) and prostaglandins (PGE2, PGD2) regulate monocyte and neutrophil functions. Activated platelets also release dioxolane A3 (DXA3) following PAR1‐PAR4 activation or by collagen, ionophore, or collagen‐thrombin combination employing cPLA2 and AA metabolism (Figure A), independent of TxA2 synthesis. DXA3 generation is affected by genetic deficiency of cPLA2, by cPLA2, and COX‐1 inhibitors (aspirin, indomethacin), but is enhanced in 12‐LOX −/− murine platelets .…”
Section: Platelets and Lipids: Age‐old Accomplicesmentioning
confidence: 99%
“…Activated platelets also release dioxolane A3 (DXA3) following PAR1‐PAR4 activation or by collagen, ionophore, or collagen‐thrombin combination employing cPLA2 and AA metabolism (Figure A), independent of TxA2 synthesis. DXA3 generation is affected by genetic deficiency of cPLA2, by cPLA2, and COX‐1 inhibitors (aspirin, indomethacin), but is enhanced in 12‐LOX −/− murine platelets . DXA3 is rapidly esterified to 16:0‐, 18:1‐, 18:0‐PE‐plasmalogen, and 18:0‐acyl‐PE by lysophospholipid acyltransferases (Figure A); so mostly remains platelet associated, while free DXA3 adds to serum levels during clotting.…”
Section: Platelets and Lipids: Age‐old Accomplicesmentioning
confidence: 99%